Gender Differences in Impoliteness Strategies on TikTok Comments: A Pragmatic Study - Saragih, Natanael; Amaniarsih , Dwi Suci; Asrul , Nurmahyuni; Murni, Sri Minda (EXCELLENCE: Journal of English and English Education, 2025)
This study investigates gender differences in the use of impoliteness strategies in TikTok comment sections from a pragmatic perspective. Drawing on Culpeper’s (1996, 2011) impoliteness framework, this research aims to identify the types of impoliteness strategies employed by male and female TikTok users and to examine how these strategies are realized in online interaction. The data consist of 218 impolite comments collected from selected viral TikTok videos. A qualitative descriptive approach was employed to analyze the pragmatic functions of impoliteness strategies, supported by quantitative analysis to examine frequency patterns across genders. The findings reveal that both male and female users actively engage in impolite discourse; however, they differ in their preferred strategies. Male commenters tend to employ more direct and explicit strategies, particularly bald on record and negative impoliteness, while female commenters predominantly use indirect strategies such as sarcasm or mock politeness and positive impoliteness. These differences suggest that impoliteness on TikTok functions as a strategic communicative resource shaped by gender, platform affordances, and interactional goals. The study concludes that impoliteness in digital discourse is a socially meaningful phenomenon that reflects the intersection of language, power, identity, and gender in contemporary online communication.